Hermansky–Pudlak syndrome: infrequent bleeding and first report of Turkish and Pakistani kindreds. Issue 4 (1st April 2002) - Harrison, C; Khair, K; Baxter, B; Russell-Eggitt, I; Hann, I; Liesner, R
Abstract : Hermansky–Pudlak syndrome (HPS) is a rare disorder characterised by oculocutaneous albinism, a bleeding tendency, and lipofuscinosis. This retrospective study reviews the clinical history and haematological features of 23 cases of HPS. Information was gathered from patient notes and by direct interview. Thirteen of the 23 children were of Turkish origin, 12 being members of four kindreds from the Turkish/Kurdish border. Four children originated from Pakistan. Haemorrhage was uncommon; two experienced significant bleeding (intracranial and retinal haemorrhage in one and menorrhagia in another), and twelve minor symptoms. Results of laboratory evaluation of platelet function were not predictive of bleeding; in particular the PFA-100 analyser was not sensitive to the HPS defect. The most sensitive test of platelet fuction was quantitation of platelet nucleotides. The occurrence of Turkish and Pakistani kindreds with HPS is novel and follow up for long term complications described in Puerto Rican patients as well as genetic analysis is ongoing.